A note on the non-commutative laplace-varadhan integral lemma - De Roeck, Wojciech; Maes, Christian; Netočný, Karel; Rey-Bellet, Luc (Reviews in mathematical physics, 2010)
We continue the study of the free energy of quantum lattice spin systems where to the local Hamiltonian H an arbitrary mean field term is added, a polynomial function of the arithmetic mean of some local observables X and Y that do not necessarily commute. By slightly extending a recent paper by Hiai, Mosonyi, Ohno and Petz [10], we prove in general that the free energy is given by a variational principle over the range of the operators X and Y. As in [10], the result is a non-commutative extension of the Laplace-Varadhan asymptotic formula.